Patterning of tensile fabric structures with a discrete element model using dynamic relaxation. (June 2016) - Gale, Stuart; Lewis, Wanda J.
Highlights: A discussion of computational patterning is presented. A new patterning method, using a discrete model, is proposed. Comparisons are drawn with published results. The suitability of discrete models for patterning are demonstrated. Abstract: Tensile fabric membranes present opportunities for efficient structures, combining the cladding and support structure. Such structures must be doubly curved to resist external loads, but doubly curved surfaces cannot be formed from flat fabric without distorting. Computational methods of patterning are used to find the optimal composition of planar panels to generate the form, but are sensitive to the models and techniques used. This paper presents a detailed discussion of, and insights into, the computational process of patterning. A new patterning method is proposed, which uses a discrete model, advanced flattening methods, dynamic relaxation, and re-meshing to generate accurate cutting patterns. Comparisons are drawn with published methods of patterning to show the suitability of the method.